(untitled) (2015)
This paper intends to show how John Rawls' political philosophy, based on A Theory of Justice and further works, represents a theoretical proposition in favor of a Liberal society and a fair political order. His theoretical project represents a reformulation of classical liberalism, which has prompted several reviews and strong opposition, even from the same Liberal quarters. Surviving those criticisms, in fact, is the source of the great prestige Rawls' work in the academic world. We intend to do a theoretical approach to the bastions of Rawls' theory. This approach argues for the possibility of defending a Liberal conception of contemporary political philosophy without losing its self-critical capacity.